Bioerosion in a changing world: a conceptual framework. (4th January 2018) - Davidson, Timothy M.; Altieri, Andrew H.; Ruiz, Gregory M.; Torchin, Mark E.
Abstract: Bioerosion, the breakdown of hard substrata by organisms, is a fundamental and widespread ecological process that can alter habitat structure, biodiversity and biogeochemical cycling. Bioerosion occurs in all biomes of the world from the ocean floor to arid deserts, and involves a wide diversity of taxa and mechanisms with varying ecological effects. Many abiotic and biotic factors affect bioerosion by acting on the bioeroder, substratum, or both. Bioerosion also has socio‐economic impacts when objects of economic or cultural value such as coastal defences or monuments are damaged. We present a unifying definition and advance a conceptual framework for (a) examining the effects of bioerosion on natural systems and human infrastructure and (b) identifying and predicting the impacts of anthropogenic factors (e.g. climate change, eutrophication) on bioerosion. Bioerosion is responding to anthropogenic changes in multiple, complex ways with significant and wide‐ranging effects across systems. Emerging data further underscore the importance of bioerosion, and need for mitigating its impacts, especially at the dynamic land–sea boundary. Generalised predictions remain challenging, due to context‐dependent effects and nonlinear relationships that are poorly resolved. An integrative and interdisciplinary approach is needed to understand how future changes will alter bioerosion dynamics across biomes and taxa.